IN VITRO PHOTODYNAMIC INACTIVATION OF MYCOBACTERIUM TUBERCULOSIS BY RADAHLORIN - D. A. Bredikhin; S. D. Nikonov; A. G. Cherednichenko; T. I. Petrenko (Туберкулез и болезни лёгких)
Goal: to detect the best mode of in vitro photodynamic inactivation of M. tuberculosis by Radahlorin.Subjects and methods. The activity of culture of M. tuberculosis, H37Rv strain, photosensitized by 0.00005% Radohlorin was compared and the intensity of growth was assessed after photodynamic inactivation by different doses of light energy with 662 nm wavelength.Results. For the first time, anti-microbial properties of E6 chlorine in the form of medicamental photosensitizer (0.00005% Radohlorin) suppressing museum strain of M. tuberculosis of H37Rv were detected. Photoinactivation of M. tuberculosis depends on the dose and achieves its maximum in 10 minutes of light exposure with light energy of 0.5 W.